Latin American constitutionalism, 1810-2010 : the engine room of the constitution - Gargarella, Roberto, 1964- (Oxford University Press, 2013)
This study of 200 years of Latin American constitutionalism (1810-2010) both presents a description and a critical analysis of what Latin Americans did with their Constitutions during those years.